Serological Evidence of Immune Priming by Group A Streptococci in Patients with Acute Rheumatic Fever - Raynes, Jeremy M.; Frost, Hannah R. C.; Williamson, Deborah A.; Young, Paul G.; Baker, Edward N.; Steemson, John D.; Loh, Jacelyn M.; Proft, Thomas; Dunbar, P. R.; Atatoa Carr, Polly E.; Bell, Anita; Moreland, Nicole J. (Frontiers in Microbiology, 2016)
Acute rheumatic fever (ARF) is an autoimmune response to Group A Streptococcus (GAS) infection. Repeated GAS exposures are proposed to ‘prime’ the immune system for autoimmunity. This notion of immune-priming by multiple GAS infections was first postulated in the 1960s, but direct experimental evidence to support the hypothesis has been lacking. Here we present novel methodology, based on antibody responses to GAS T‑antigens, that enables previous GAS exposures to be mapped in patient sera. T-antigens are surface expressed, type specific antigens and GAS strains fall into 18 major clades or T-types. A panel of recombinant T-antigens was generated and immunoassays were performed in parallel with serum depletion experiments allowing type-specific T‑antigen antibodies to be distinguished from cross-reactive antibodies. At least two distinct GAS exposures were detected in each of the ARF sera tested. Furthermore, no two sera had the same T-antigen reactivity profile suggesting that each patient was exposed to a unique series of GAS T‑types prior to developing ARF. The methods have provided much-needed experimental evidence to substantiate the immune-priming hypothesis, and will facilitate further serological profiling studies that explore the multifaceted interactions between GAS and the host.